ENTREPRENEURSHIP AND TRAINING OF READING STUDENTS (Fiep Bulletin - online, 2020)
The current scenario requires the school to develop a curriculum that contributes to the training of active and autonomous students. In this context, working Entrepreneurial Pedagogy through reading becomes a fundamental stimulus, because the active and technological student needs to be motivated. Therefore, it is important that the Characteristics of Entrepreneurial Behaviors are stimulated, as they excel in encouraging the autonomy of the student, articulating, therefore, the competences of the National Curriculum Base. In this sense, these two proposals consider that communication, information and reading modify the reality of the student. Thus, a proposal with reading can relate to the assumptions of Entrepreneurial Pedagogy, leaving the school with innovation of practices that develop reading, contributing for students to read critically and autonomously. Given this, the present study analyzes reading activities with students of Elementary School II, from E M Marphiza Magalhães Santos, public institution of Santa Bárbara, Minas Geprepreneurism, Learning Autonomy.
Keywords: ÉDUCATION À L'ENVIRONNEMENT; LA PRATIQUE PÉDAGOGIQUE ET SON APPLICATION DANS LES ÉCOLES PUBLIQUES